Dark Triad Personality Identification on Napoleon: An Analysis of “Animal Farm”, Novel by George Orwell - Lyandi Putra, Yakub; Rahman, Irpan Ali (e-LinguaTera, 2024)
This paper discusses the manifestation of Dark Triad Personality on Napoleon character in George Orwell’s Animal Farm. Applying qualitative research method, this research analyzed the dark personality traits found in the conducted literary works, written by George Orwell and published by Penguin Books in 2008. This particular research aims is attempted to examine how dark triad personality of Napoleon was manifested in the Novel. Hereby, the findings showed that first is Narcissism, portrayed by his tendency to be a self-centered persona in every situation possible. Napoleon wants to get the highlight of farm’s achievement, also to show the self-superiority towards other animals. The second is Machiavellianism, this traits portrayed by utilizes his position as an authoritarian leader in order to get absolute control and committed propaganda to gain advantageous situation on the farm. The third is Psychopathy, shown by him in the form of violence and subtle slavery on the farm. On his leadership, it seems like no empathy to all animals who conduct a work in the farm. Nevertheless, he use violence as a threatening tool, especially when he conduct an execution as a presumption of involvement to Snowball’s rebellion. In conclusion, this study highlights that the dark triad personality in Animal Farm novel arguably can be delivered in the form of fictional character. Dark Triad Personality are merely impactful devices in literary works that can embrace characters darker side of human nature. Analyzing literary works with specific personality theory may provide deep knowledge and understanding of characters personality.